Analisis Pengaruh Mutu Pelayanan terhadap Pemanfaatan Ulang Pelayanan Rawat Inap di Rumah Sakit X - Albert Hasibuan; I.Gusti Ngurah.Y.Usdayana; Halisa Kurniati; Fransiscus A.C.Wakumoan (Jurnal Rumpun Ilmu Kesehatan, 2025)
In perceiving the quality of service, satisfaction, or image, a person would base the perception on the values felt by the patients. The research aimed at analyzing the influence of service quality on the reuse of inpatient services at Hospital X. This was an analitic survey research with the cross sectional study design. Responden taken as samples were as many as 120 people. Data collected through an interview, questionnaire, and documentation. Data were analyzed using the descriptive statistics analysis namely calculating the average, percentage, frequency tables and inferential statistics through the Chi-square test, multivariate analysis through the multiple logistic regression analysis. The research result indicates that the influence of service quality with the inpatient reutilization in general hospital X was significant, that is service quality of administration (p = 0,032), service quality of doctors (p = 0,001), service quality of nurses (p = 0,000), service quality of pharmacist (p = 0,000), service quality of instruments (p = 0,020), and quality service of treatment rooms (p = 0,009). The variable of the nurses service quality and pharmacist’s quality are the most influential variables on quality service with the inpatient reutilization.